COMPUTER SIMULATION OF PERFORMANCE OF “IZMIR” MEASURING COMPUTER SYSTEM IN HIGH-SPEED LSI/VLSI - Новосядлий, Степан Петрович; Терлецький, Андрій Іванович; Фрик, Оксана Богданівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The possibilities of improving of performance both LSI/VLSI and computer measuring systems by decreasing of operating temperature to cryogenic level for cases of high conductive or superconducting wiring. It was shown that system performance depends on parameters of connecting lines and structures of active elements LSI/VLSI at cryogenic temperatures due to the growing mobility of charge carriers. It was demonstrated also that the use of superconducting wiring (routing) is effective only on condition of significant improvement options SFETs as active elements LSI (memory, microprocessors, microcontrollers, etc.).